2020
DOI: 10.1159/000513180
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 Virus Manifestations in the Gastrointestinal Tract: Therapeutic Implications

Abstract: <b><i>Background:</i></b> About 1 year ago a novel virus – SARS-CoV-2 – began to spread around the world. It can lead to the disease COVID-19, which has caused more than 1 million deaths already. <b><i>Summary:</i></b> While it was first recognized as a disease leading to pneumonia and lung failure, we know by now that COVID-19 is more complex. COVID-19 is a systemic hyperinflammatory disease affecting not only the lungs, but also many other organs. Especially th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…The influence of SARS-CoV-2 infection on the GI system is well-established, with main symptoms being diarrhea, abdominal pain, loss of appetite, vomiting, nausea, and loss of taste ( Jefremow and Neurath, 2021 ). However, onset of lymphocytic colitis has been observed rarely following SARS-CoV-2 infection with consistently elevated levels of fecal calprotectin and persistent diarrhea, even in the absence of fecal SARS-CoV-2 RNA ( Nassar et al, 2019 ).…”
Section: Sars-cov-2 Infection and Vaccinationmentioning
confidence: 99%
“…The influence of SARS-CoV-2 infection on the GI system is well-established, with main symptoms being diarrhea, abdominal pain, loss of appetite, vomiting, nausea, and loss of taste ( Jefremow and Neurath, 2021 ). However, onset of lymphocytic colitis has been observed rarely following SARS-CoV-2 infection with consistently elevated levels of fecal calprotectin and persistent diarrhea, even in the absence of fecal SARS-CoV-2 RNA ( Nassar et al, 2019 ).…”
Section: Sars-cov-2 Infection and Vaccinationmentioning
confidence: 99%
“…Prior studies have also suggested that the mechanism responsible for the imbalance in the gut microbiome during respiratory infection is likely by induction of type I interferons (IFNs) [ 99 ]. Indeed, it is known that patients with SARS-CoV-2 infection suffering from ARDS also exhibit gastrointestinal symptoms, such as diarrhea, vomiting, nausea, and abdominal pain [ 100 ], which may be related to similar mechanisms.…”
Section: Evidence For Potential Benefits Of Plant-derived Bioactivesmentioning
confidence: 99%
“…Their inhibition damages the virus entering and, consequently, the cytokine storm. Currently, some clinical trials are using JAK’s inhibitors to treat COVID-19 [ 93 , 94 ]. Baracitinib has a double action.…”
Section: Drugs and Inflammatory Bowel Diseases: What Have We Learned?mentioning
confidence: 99%